Hasil Garut (Marantha Arundinaceae) pada Kekeringan - Muhammad Bogi Oktafani; Supriyono Supriyono; Mth Sri Budiastuti (Agrotechnology Research Journal, 2017)
Arrowroot (Marantha arundinaceae) is one of substitute food source of wheat flour and rice. Mostly arrowroot wildly grow in yard and forest untreated so its productivity is relatively low. During the dry season, water availaility drops, causing drought. The aim of this research is to determine the effect of drought stress on tuber yields of arrowroot. This research was conducted on March to September 2016 at the Faculty of Agriculture Land Experiment Field of Sebelas Maret University in Jumantono, Karanganyar. The study using a randomized completed block design (RCBD) and one research have one treatment factor. One treatment has 4 experimental levels and each level is repeated six times so that there are 24 experimental unit. Drought treatment consist of following levels; 100%, 75%, 50%, 25% of field capacity. The research shows that arrowroot is a dry-resistant plant up to 25% and produces good growth and yield is indicated by tuber weight (551,67g).